Farmers Perception and Propensity for Adoption of Integrated Pest Management Practices in Vegetable Cultivation - Wason, Monika; Padaria, R. N.; Singh, Baldeo; Kumar, Anjani (Indian Journal of Extension Education, 2022)
Promotion of integrated pest management (IPM) has been emphasized to contain chemical pesticide led hazard to health as well as environment. The study aimed at examining vegetable growers perception and prosperity to adopt IPM. Farmers having propensity to adopt differed significantly with those having no propensity to adopt with respect to perception about IPM as revealed by their endorsement pattern to the statements like "IPM practices may ruin the crop and incur heavy losses" (p